2019
DOI: 10.1002/adma.201901071
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Biomaterials and Technologies for Vascular Embolization

Abstract: Minimally invasive transcatheter embolization is a common nonsurgical procedure in interventional radiology used for the deliberate occlusion of blood vessels for the treatment of diseased or injured vasculature. A wide variety of embolic agents including metallic coils, calibrated microspheres, and liquids are available for clinical practice. Additionally, advances in biomaterials, such as shapememory foams, biodegradable polymers, and in situ gelling solutions have led to the development of novel pre-clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
189
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(216 citation statements)
references
References 488 publications
(440 reference statements)
1
189
0
4
Order By: Relevance
“…S1I †), which were comparable to the loading capacity of commercial microspheres. 9,10 As platforms designed with a thermal-triggered release property, the cumulative release of DOX from P(AAm-co-AN) and P(AAm-co-AN)/(SPION@PDA) microspheres at 37°C after 7 days were only 3.85% and 3.05%, respectively, indicating the good storage stability of these drug-loaded microspheres (Fig. 3E).…”
Section: Drug Loading and Release Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…S1I †), which were comparable to the loading capacity of commercial microspheres. 9,10 As platforms designed with a thermal-triggered release property, the cumulative release of DOX from P(AAm-co-AN) and P(AAm-co-AN)/(SPION@PDA) microspheres at 37°C after 7 days were only 3.85% and 3.05%, respectively, indicating the good storage stability of these drug-loaded microspheres (Fig. 3E).…”
Section: Drug Loading and Release Profilesmentioning
confidence: 99%
“…6,7 Therefore, the performance of the chemoembolization vectors is the key determinant of TACE outcome. [8][9][10] The major goal of TACE is to achieve complete tumor necrosis, thus providing patients with survival benefits as much as possible. It has been demonstrated that the magnitude of tumor necrosis, in terms of treatment response which is usually assessed by contrast enhanced imaging studies, correlated closely with prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main method to achieve endovascular embolization of arteries in pigs has been the injection of autologous blood clots to extracranial vessels [ 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ]. The embolization of an artery implies the reduction of its blood flow [ 142 ]. For instance, bilateral thromboembolism to reduce blood flow in both ascending pharyngeal arteries caused multiple and variable focal areas of stroke damage, although consistent temporo-parietal infarcts were not generated as seen by diffusion-weighted imaging [ 127 ].…”
Section: Interventions To Induce Ischemic Strokes In Pigsmentioning
confidence: 99%
“…[ 5 ] To solve the problems, a variety of modified coils have been proposed, such as Cerecyte Coils, Axium Detachable Coil system, Matrix and Matrix2 Detachable Coils, HydroCoil, and HydroSoft. [ 6–11 ] Among them, the hydrogel coated coils were designed mainly to increase the packing density by using a hydrogel coating that expanded in the presence of blood. [ 12 ] Although excellent packing density of 64–85% was achieved by hydrogel‐coated coils, the early gel expansion and concurrently increased friction make it difficult for the clinician to deploy the modified coils.…”
Section: Introductionmentioning
confidence: 99%